Safety and Efficacy of BIND-014, a Docetaxel Nanoparticle Targeting Prostate-Specific Membrane Antigen for Patients With Metastatic Castration-Resistant Prostate Cancer: A Phase 2 Clinical Trial - Autio, Karen A; Dreicer, Robert; Anderson, Justine; Garcia, Jorge A; Alva, Ajjai; Hart, Lowell L; Milowsky, Matthew I; Posadas, Edwin M; Ryan, Charles J; Graf, Ryon P; Dittamore, Ryan; Schreiber, Nicole A; et al. (JAMA oncology, 2018)
Preferential delivery of docetaxel to tumors by prostate-specific membrane antigen (PSMA)-targeted nanoparticles is clinically effective, and the selective reduction of PSMA-positive circulating tumor cells (CTCs) after treatment has implications for patient selection and disease monitoring. To determine the safety and efficacy of BIND-014, a PSMA-directed docetaxel-containing nanoparticle, in patients with metastatic castration-resistant prostate cancer (mCRPC). A multicenter open-label, phase 2 clinical trial of 42 chemotherapy-naive patients with progressing mCRPC after treatment with abiraterone acetate and/or enzalutamide was conducted from June 24, 2013, to June 10, 2016. Treatment with BIND-014 at a dosage of 60 mg/m2 was given intravenously on day 1 of 21-day cycles in combination with prednisone until disease progression or unacceptable toxic effects occurred. The primary end point was radiographic progression-free survival according to Prostate Cancer Working Group 2 recommendations and Response Evaluation Criteria in Solid Tumors, version 1.1. Secondary end points included prostate-specific antigen (PSA) response (≥50% reduction from baseline) and changes in CTC number (from ≥5 to <5 cells per 7.5 mL of blood) (CellSearch). Changes in CTC number based on PSMA expression levels on CTCs were also evaluated (Epic Sciences). Among the 42 patients (81% white), the median age was 66 (range, 50-85) years, and median number of doses received was 6 (range, 1-21). A PSA response was observed in 12 of 40 patients (30%; 95% CI, 18%-45%), measurable disease response in 6 of 19 (32% [95% CI, 15%-54%]), and CTC conversions in 13 of 26 (50%; 95% CI, 32%-68%). Median radiographic progression-free survival was 9.9 (95% CI, 7.1-12.6) months. With use of the Epic Sciences non-EPCAM-based CTC detection platform, CTCs were detected in 16 of 18 patients (89%); 11 of 18 (61%) had CTCs with PSMA expression above the analytical threshold level (PSMA positive) at baseline (range, 0.4-72.4 CTCs/mL). After treatment, PSMA-positive CTCs were preferentially reduced. Treatment-related adverse events included grade 1 or 2 fatigue (29 of 42 patients [69%]), nausea (23 [55%]), neuropathy (14 [33%]), and neutropenic fever (1 [2%]). These findings suggest that treatment with BIND-014 is active and well tolerated in patients with chemotherapy-naive mCRPC. Antitumor activity may be related to PSMA expression levels on CTCs, which suggests that patients who are likely to benefit from this treatment can be identified before treatment is initiated. ClinicalTrials.gov Identifier: NCT01812746.